(untitled) (Acta Scientiarum. Technology, 2023)
Studying new microbial sources and evaluating the growth kinetics behavior to predict large-scale production become essential. Besides, research with low-cost culture media has gained interest due to the need to decrease enzyme production costs. The literature concerning the use of macromycetes as a source of amylases, and applying mathematical models to predict their behavior is scarce. In this study, four growth kinetics in different compositions of culture media were carried out: two of them using different concentrations of Low-Grade Flour (LGF), one wheat mill by-product and two synthetic ones. In the kinetics mathematical models were used to evaluate the bioprocesses and their scaling feasibility. Mathematical models, such as modified Logistic, modified Gompertz, Baranyi, and Roberts, and modified Luedeking-Piret, were applied to predict mycelial growth, enzyme production, and substrate consumption. The results showed the model´s capability to predict mycelial growth (biomass) and substrate consumption (starch concentration). On the other hand, the mathematical models efficiently describe only the maximum enzymatic activity (Î±-amylase), not the process’s other parameters, because of the complexity and diversity of biomolecules synthesized by Coprinus comatus. The wheat mill by-product was efficient as an ingredient in the culture media composition. Furthermore, it was concluded that B2 formulation (culture medium with 48.5 g/L of LGF) is the batch with the highest potential for the Î±-amylase production from C. comatus and the expansion of this process on an industrial scale. This study is important and valid for the scientific community since modeling studies for macromycetes are scarce in the literature.